Investigation of dielectric and electrical properties of tungsten doped Bi2/3Cu3Ti4O12 ceramics - Jena B.; Prajapati D.; Rai V.S.; Verma H.; Upadhyay S.; Singh N.B.; Kumar A.; Tiwary D.; Mandal K.D. (My University, 2025)
Enhancing dielectric materials is crucial to the progress of energy storage technology. This work addresses the impacts of tungsten (W) substitution on the dielectric, electrical characteristics, and microstructure of ceramics called Bi2/3Cu3Ti4O12 (BCTO). The W-doped BCTO ceramics were fabricated employing a semi-wet method and sintered for eight hours at 1173 K. The synthesized Bi2/3Cu3Ti4-xWxO12 (x = 0.00, 0.05, 0.10, 0.20) labelled as BCTWO ceramics' phase development with minor secondary phase was validated by X-ray diffraction. X-ray photoelectron spectroscopy (XPS) was utilized to figure out the oxidation states of the elements, while energy-dispersive X-ray spectroscopy (EDX) analysis was employed to verify phase purity. The addition of a modest amount of W dopant decreased the grain size of BCTWO ceramics, most likely as a result of greater oxygen vacancy production during sintering, as shown by scanning electron microscopy (SEM) pictures. The surface texture was investigated by employing an atomic force microscope (AFM). The BCTO ceramic doped with tungsten (W) revealed an average grain size of 2.18 µm, which was greater than the un-doped BCTO ceramic. This could result in a higher dielectric constant (ɛʹ) and loss tangent (tan δ) in Bi2/3Cu3Ti4-xWxO12(x = 0.05, 0.1, 0.2) ceramics. The BCTWO ceramic with higher dopant concentration was found to have a relatively high loss tangent (tan δ ~ 2.58 at 303 K and 1 kHz) and a high dielectric permittivity (εʹ ~ 7.8 × 103). © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.